ANALISIS TANGGUNG JAWAB PERUSAHAAN PENERBANGAN TERHADAP KERUGIAN PENUMPANG AKIBAT HILANGNYA BAGASI TERCATAT YANG MEMUAT BARANG BERHARGA TANPA SEPENGETAHUAN PENGANGKUT BERDASARKAN KONVENSI WARSAWA 1929 SEBAGAI LEX SPECIALIS - Hendra Winata; H. K. Martono (Fakultas Hukum Universitas Tarumanagara, 2019)
Aircraft as air carrier of persons, luggage or goods which receive any amount of payment from the passengers to carry any passengers from the place of departure to the place of destination. The carrier is liable for damage sustaind in the event of the death or wounding of the passenger or other bodily injury, of the destruction or lost of,or of damage to registered luggage if the accident which caused the damage took place during the carriage by aircraft. In the carriage of registered luggage, the liability of the carrier is limited to the amount regulated both at international conventions or national regulation. Unless at the time when the luggage was handed over to the carrier, the passengers or the consignor has declared the contents and the value of the registered luggage and the carrier agreed to carry the registered luggage and the passengers or the consignor has paid a supplementary sum. If the passengers or the consignor at the time when the luggage was handed over to the carrier has declared the contents and the value of the registered luggage, in terms of any destruction, lost of, or of damage to registered luggage, the passengers or the consignor entitled to receive compensation of the amount regulated both at international conventions or national regulation and the sum of the actual value of the registered luggage